Border Tuner and Teeter-Totter Wall: Two works of participatory public pedagogy. Issue 1 (1st June 2021) - Kaplan, Heather G.
This article looks at two socially engaged art works, Teeter-Totter Wall by Ronald Rael and Virginia San Fratello and Border Tuner by Rafael Lozano-Hemmer that challenge dualistic notions of self and other, public and private, and national and multinational. Each work proffers a perspective of the US-Mexico border that counters those communicated through national political rhetoric and common in popular media reporting. This article not only recognizes these works as art but also as public pedagogy, or works accessible to the broader public and community that function to teach us something or to reframe or expand our understanding and to question or resist dominant narratives. In addition to questioning totalizing narratives, this article considers intersecting notions of the public on the border. Recognizing that the border occupies simultaneous and varied notions of the public in terms of being a site of local culture, a symbol of national debate, a firestorm of divisive rhetoric and an international marker of global politics and economics, this article considers how differing sites of public pedagogy function.